ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN LOYALITAS PASIEN DI RUMAH SAKIT - Miftahul Jannah; Anindita Paramastuti Azuma; Zulrahmatulhuda Zulrahmatulhuda; Surya Syarifuddin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: The year-over-year increase in the number of hospitals can lead to increasingly fierce competition among healthcare facilities. The growing number of hospitals—both general and specialized—means that every healthcare institution must compete to provide the best possible service to the public. The objective of this study is to analyze the factors associated with patient loyalty in hospitals. This study employed a cross-sectional design. The research was conducted at a hospital in Bima City. The study was conducted in April 2025. The study population consisted of all patients in the outpatient department. The sample comprised 100 respondents. Purposive sampling was used. The research instrument used was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a relationship between satisfaction with physical evidence (p-value: 0.042) and satisfaction with responsiveness (p-value: 0.034) and patient loyalty. It is recommended that the hospital further improve the quality of its services to create a positive perception, thereby increasing patient loyalty.Keywords: Tangible Evidence, Responsiveness, Loyalty